Polymorphisms in ovine ME1 and CA1 genes and their association with feed efficiency in Hu sheep. (15th February 2021) - Zhang, Deyin; Zhang, Xiaoxue; Li, Fadi; Yuan, Lvfeng; Zhang, Yukun; Li, Xiaolong; Zhao, Yuan; Song, Qizhi; Li, Guoze; Wang, Weimin
Abstract: Improving feed efficiency would increase profitability for producers. The objective of this study was to detect the expression levels of ME1 and CA1 and the polymorphisms of ME1 and CA1 associated with the feed conversion ratio (FCR) and residual feed intake (RFI) of Hu sheep by using qRT‐PCR, pooled DNA sequencing and KASPar assay. The qRT‐PCR results indicated that the expression levels of ME1 and CA1 were significantly higher in the liver tissues of low‐RFI sheep than in those of the high‐RFI sheep ( p <.01). Association analysis demonstrated that the polymorphism ME1 g.453 C > T was significantly associated with FCR and RFI ( p <.05). The polymorphism CA1 g.199 C > T had a significantly associated with FCR ( p <.05) and no association with RFI ( p >.05). Significant differences were observed between the combined genotypes and FCR and RFI at different measurement periods ( p <.05). Thus, we propose the use of these two polymorphisms as new candidate molecular markers for improving feed efficiency in sheep populations.